A violência em espaço escolar: o que dizem pesquisas brasileiras (2001-2010) - Diniz, Julia Elaine [UNESP] (2015)
This research was developed in the scope of the surveys that have been produced in the past ten years by a group called Grupo de Pesquisa sobre Educação Escolarizada a partir das ideias de Pierre Bourdieu (CNPq). It establishes a straight relation to a project called Violência por professores e professoras na voz de suas vítimas: uma estrutura do habitus profissional em professores brasileiros, sponsored by FAPESP, process number 2010/11054-6. My undergraduate research, also sponsored by FAPESP, process number 2012/04119-0 was executed in this same project and it was from this activity that the present project evolved. Yet, this research is related to another project titled O que alunos dizem sobre a participação, ou não, de professores na produção do fenômeno violência em meio escolar: buscando a complexidade da constituição do fenômeno, sponsored by CNPq, process number 401083/2011-0. In this work, the aim is to deepen the understanding of the violence in the school space phenomenon through an analytical description of the searches executed between 2001 and 2010 in Brazil, with the objective of identifying, from it, who commits, who suffers, how and why it happens in the school space. It is, so, a quali-quantitative research, eminently bibliographic and with exploratory stamp. The methodological procedure comes from an inflection about the technique Content Analysis. The sources are 22 researches, in which there are twelve dissertations, two thesis, seven UNESCO researches and one Ministry of Education work. The theoretical fundament consists in works made by different authors. Phillipe Ariès contributed with a historical understanding about places, situations, conditions and positions through the child, the infancy, the adolescence, the family and the school passed, considering the violence that permeated the instances of the social life. Bernard Charlot and Pierre Bourdieu are considered the structural authors in this ...